Dual roles for DNA sequence identity and the mismatch repair system in the regulation of mitotic crossing-over in yeast - Datta, Abhijit (The National Academy of Sciences of the USA, 1997)
Sequence divergence acts as a potent barrier to homologous recombination; much of this barrier derives from an antirecombination activity exerted by mismatch repair proteins. An inverted repeat assay system with recombination substrates ranging in identity from 74% to 100% has been used to define the relationship between sequence divergence and the rate of mitotic crossing-over in yeast. To elucidate the role of the mismatch repair machinery in regulating recombination between mismatched substrates, we performed experiments in both wild-type and mismatch repair defective strains. We find that a single mismatch is sufficient to inhibit recombination between otherwise identical sequences, and that this inhibition is dependent on the mismatch repair system. Additional mismatches have a cumulative negative effect on the recombination rate. With sequence divergence of up to approximately 10%, the inhibitory effect of mismatches results mainly from antirecombination activity of the mismatch repair system. With greater levels of divergence, recombination is inefficient even in the absence of mismatch repair activity. In both wild-type and mismatch repair defective strains, an approximate log-linear relationship is observed between the recombination rate and the level of sequence divergence.